Analisis Faktor Yang Mempengaruhi Kinerja Karyawan Bagian Kas Daerah di Badan Pengelola Keungangan dan Aset Daerah (BPKAD) Pemerintah Provinsi Sumatera Utara - Mohd Haiqal Alif Ramadhani; Nurbaiti Nurbaiti (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2022)
As Regional General Treasurer, BPKAD is an agency that has responsibility for collecting regional income and channeling regional needs through the Regional General Treasury. In the regional treasury, the region regulates the adequacy of funds to finance regional expenditures. The aim of the research is to find out the work of the state civil apparatus (BPKAD), namely the qualitative method is a methodology that uses content analysis, which requires the transmission of steps in writing to achieve goals and information that is complete and objective, and has certain ways and methods according to the problem. faced. This type of research is direct research and library research. Based on the results of this study it can be concluded that the performance of employees who have performed well at the Regional Office of the Financial and Asset Management Agency (BPKAD) of North Sumatra Province can improve this good performance to also create good jobs that advance positions according to the key indicators of current North Sumatra Province BPKAD employees .And already in good improvement efforts it can be seen that the ability to use working time effectively, the quality of work carried out and employee responsibilities are good. This is because the Regional Economic Development Board administrators are able to communicate with their staff to improve service quality and provide good facilities and infrastructure ideal for advancing the development of the Second sector in the province of North Sumatra and achieving these development goals.